Assistance with Simple Bookkeeping Concepts and Marketing Strategy Innovation as Steps for Sustainability of UMKM "Gelora" Dumpling Skin Noodle Factory, Sidorahayu Village - Nurcahyadi, Khafid; Aprilian, Rifky Zahrul; Almaas, Ahmad Hamman; Alhuda, Aliyuddin (Jurnal Masyarakat Religius dan Berwawasan, 2024)
This research was conducted at the UMKM noodle and dumpling skin factory "Gelora" Sidorahayu Village, Wagir District. The purpose of writing this article is to find out the impact that the UMKM noodle and dumpling skin factory "Gelora" had after receiving socialization on simple bookkeeping including cash in and out reports, profit and loss reports and marketing strategy assistance including product photos, product price list designs and business logo designs. initiated by the 213 KKM UIN Maulana Malik Ibrahim Malang group, Sidorahayu Village. The author found the fact that the owner only carried out rough and unsystematic calculations regarding cash inflow and outflow and calculating product selling prices. The same thing also happened with the marketing strategy carried out by the owner which was less than optimal in implementing an effective marketing strategy to increase sales volume. The author hopes that after this socialization process the owner will be able to implement a better and more systematic bookkeeping system and also a marketing strategy that is suitable for the business base for the sustainability of this UMKM business.